A negative life event impairs psychosocial stress, recovery and running economy of runners - Otter, R. T. A.; Brink, M. S.; Diercks, R. L.; Lemmink, K. A. P. M. (International Journal of Sports Medicine, 2016)
The purpose was to investigate how a negative life event (NLE) affects perceived psychosocial stress, recovery and running economy (RE). Competitive runners were monitored in a prospective non-experimental cohort study over one full training season in which they experienced the same unplanned severe NLE. 16 runners recorded stress and recovery scores (RESTQ-Sport) every week. The average scores over 3 weeks before the NLE were used as a baseline and were compared to scores during the week of the NLE (week 0), week 1 and week 2. 7 runners completed a submaximal treadmill test before and after the NLE. Repeated measures ANOVAs revealed that most scores on general stress scales were increased in week 0 and 1. Of the general recovery scales, "general well-being" was decreased in week 0 and 1, "social" and "physical recovery" were decreased in week 0. No changes in the sport-specific stress scales were found. However, 2 of the sport-specific recovery scales were decreased in week 0. An impaired RE was shown 3 weeks after the NLE. Therefore, it is important to know what is going on in an athlete`s life, because stressful life events alter RE after the stress and recovery already returned to normal levels.